Lighting system design using green energy from living plants - Lee, Ming Foong; Mohd Zain, M.N.N.; Chee, Sern Lai (IOP Publishing, 2018)
Green energy is the energy generated from nature such as water, wind, solar and wave that aimed to reduce environmental damage or destruction, sustain the use of energy and natural resources as well as promote the use of renewable energy. This study aimed to analyse the electrical energy generated by the three types of living plants selected at the parking area of the Faculty of Technical and Vocational Education and design a lighting system for the parking area by using living plants as the source of energy generation. This study consisted two phases, Phase I: Analysing the energy generated from the living plants; and Phase II: designing the lighting system for the parking area phase using living plants. The result of the analysis of the energy produced by living plants showed that the selected living plants are able to produce energy with the sufficient amount needed by the lighting system at the parking area. Based on the analysis of the generation of energy from living plants, the lighting system was designed by using step-up circuit and the charging circuit. In conclusion, living plants should be fully utilized as part of the energy resources to generate energy.